A microfluidic approach for development of hybrid collagen-chitosan extracellular matrix-like membranes for on-chip cell cultures. (10th February 2021) - Rosella, Erica; Jia, Nan; Mantovani, Diego; Greener, Jesse
Abstract: To advance organ-on-a-chip development and other areas befitting from physiologically-relevant biomembranes, a microfluidic platform is presented for synthesis of biomembranes during gelation and investigation into their role as extracellular matrix supports. In this work, high-throughput studies of collagen, chitosan, and collagen-chitosan hybrid biomembranes were carried out to characterize and compare key properties as a function of the applied hydrodynamic conditions during gelation. Specifically, depending on the biopolymer material used, varying flow conditions during biomembrane gelation caused width, uniformity, and swelling ratio to be differently affected and controllable. Finally, cell viability studies of seeded fibroblasts were conducted, thus showing the potential for biological applications.